Pengaruh Rasio Likuiditas, Rasio Profitabilitas dan Rasio Pasar terhadap Kebijakan Dividen pada Perusahaan Rokok - Evelyn Wijaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The research on financial factors and its effect to dividend policy of Company which is listed in Indonesia Stock Exchange have been carried out by several researchers, but the results showed inconsistent. This research aims to test the influence of liquidity ratio, profitability ratio, market ratio, and its effect on dividend policy of Cigarette Company. The liquidity ratio proxied by Current Ratio, profitability ratio proxied by Net Profit Margin, market ratio proxied by Earning Per Share, and dividend policy proxied by Dividend Per Share. The sample used are 3 companies, listed in IDX period of 2001-2014. Data used in this study is secondary data by using financial statements. The Data analyzed using multiple linear regression. The result showed that net profit margin has a significant effect on dividend per share whereas current ratio and earnings per share has no significant effect on dividend per share of cigarette company which listed in IDX period of 2004-2014. Keywords : Liquidity Ratio, Profitability Ratio, Market Ratio, Dividend Policy.